Input From Practice: Reshaping Dental Education for Integrated Patient Care - MacNeil, R. Lamont (Monty); Hilario, Helena (Frontiers in Oral Health, 2021)
Among the primary challenges in advancing the practice of integrated primary dental and medical health care is the appropriate educational and clinical preparation of a dental workforce that can function and flourish within integrated care environments. Most dental schools train to traditional concepts and standards of dental care delivery which may be inconsistent with those of integrated care and could deter the entry and retention of graduates in contemporary, non-traditional practice models. To better understand how the dental school curriculum should be modified to accommodate integrative care models, a number of patient care organizations actively engaged in dental-medical integration were site visited to gain insight into the readiness of newer graduates, with emphasis on the DMD/DDS graduate, to function in integrated practice. Leaders, practicing clinicians and staff were interviewed and common observations and themes were documented. Conclusions and recommendations from this interview series were recently published in a five-part Special Report in the Journal of Dental Education.(1–5) This current manuscript will focus on those educational components that integrated care organizations identify as absent or inadequate in current dentist training which must be addressed to meet the unique expectations and requirements of integrated patient care. These changes appear pivotal in the preparation of a dental clinician workforce that is respectful and receptive to new practice concepts, adaptative to new practice models, and competent in new care delivery systems.